Inspiration for the Didactics of Philosophy from the First Czechoslovak Republic - Baar, Vojtěch Lubomír (Civilia, 2023)
The conference paper presents a comprehensive overview of First Republic discourse on philosophy didactics. It analyses the most popular initiatives during the First Republic, particularly those of Josef Ludvík Fischer. His proposition is well developed, and a critique of the time's authors is presented. For the sake of completeness, the historical development is briefly introduced and commented on.
Keywords: Didactics of Philosophy; Philosophy; J. L. Fischer; School curriculum